Relationship between Adversity Quotient and English Proficiency at the English Language Teaching Department - Agil Abdur Rohim; Siusana Kweldju (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This quantitative study examined the role of AQ on English proficiency. The four dimensions of AQ named Control (x1), Ownership (x2), Reach (x3) and Endurance (x4) were independent variables while TOEIC score (y) was dependent variable. The subjects were 77 students of ELT Department. The result showed that AQ had influenced 15.9% (R2 = .159) to TOEIC score. There was significant influence of CORE to TOEIC score simultaneously (F>Ftable=3.44>2.33). Nevertheless, the result of partial regression analysis showed only Control (t>ttable=2.89>1.66) had significantly influenced TOEIC. Thus, this research had statistically proven that AQ provided minor contribution to students’ English Proficiency.Abstrak: Penelitian kuantitatif ini menguji pengaruh Kecerdasan Adversiti terhadap kecakapan berbahasa Inggris. Empat dimensi Kecerdasan Adversiti, yakni kontrol (x1), kepemilikan (x2), pencapaian (x3), dan ketahanan (x4) adalah variabel bebas sementara skor TOEIC adalah variabel terikat. Hasil menunjukkan bahwa Kecerdasan Adversity berpengaruh 15.9% (R2 = .159) terhadap skor TOEIC. Terdapat pengaruh signifikan emapt dimensi Kecerdasan Adversiti terhadap skor TOEIC secara simultan (F>Ftable=3.44>2.33). Namun, hasil regresi parsial menunjukkan hanya kontrol (t>ttable=2.89>1.66) yang memberikan pengaruh signifikan terhadap skor TOEIC. Penelitian ini telah membuktikan secara statistik bahwa Kecerdasan Adversity hanya memberikan kontribusi minor terhadap kecakapan siswa berbahasa Inggris.